JAN KAPISTRAN W „ANNALES...” JANA DŁUGOSZA - Kowalska, Barbara (Saeculum Christianum. Pismo Historyczne, 2017)
Jan Długosz in his cards made a presentation of Annales…fifteenth century priest and reformer – Jan Kapistran. My purpose was to show the characteristic this person, something valued by chronicle writers. Długosz used different methods, to convince the reader about theconcepts of hero sainthood, for example descriptions such as: famous, reverend, smart-which come from the catalog, which were used by the author many times, symbolical, numbers – three, forty, a hundred, which enforce belief, that next to Jan amazing things are happening. Miracle making, prediction, healing, gift of tiers most appeared in this source biography. Comparing the preacher to St. Augustine strengthened the belief in the sanctity of the hero.